Pelatihan Pemasaran Produk Secara Online Berbasis Marketplace Bagi Siswa/I Dalam Merespon Perubahan Perilaku Konsumen Di Era Digital 5.0 di SMK Negeri 2 Kutacane - Sanjaya Alcsel; Geri Suherman; Jaka Syahputra; Khairuddin Nasution (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
The aim of this community service is to improve the skills of students at SMK Negeri 2 Kutacane in maximizing Media Marketplace Technology. Where these skills can provide benefits to students in improving their skills in entrepreneurship and increasing income. The problem faced by the service team is the lack of insight by students in using Marketplace Technology. Participants who took part in the activity were students and student supervisors in the school's BLUD program who were active in using their smartphones. In this digital era, all activities are online. With optimal knowledge, matters will be easier both within the school environment and outside parties. There is a lot of potential for students at school that can be promoted online. Several marketplaces can be an option according to your needs. This community service activity not only explains the material but also directly provides practice via the participants' smartphones. BLUD students must have high creativity in improving a more decent life, improving and advancing the school. Students and the local environment will experience many things if they master the use of smartphones optimally and truly according to their needs. The most important thing is that the income based on purchases will increase. The participants were very enthusiastic about participating in the activities, both delivering material and training in the use of Marketplace Technology.